2016
DOI: 10.1097/mph.0000000000000653
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socioeconomic Factors on the Outcome of Childhood Acute Lymphoblastic Leukemia (ALL) Treatment in a Low/Middle Income Country (LMIC)

Abstract: Survival for childhood acute lymphoblastic leukemia (ALL) has improved significantly, but these benefits may not be available to many children from low and middle income countries, where reasons for treatment failure may be unique to their environment. We retrospectively reviewed data on pediatric (1 to 18 y or younger) patients with newly diagnosed ALL treated over 5 years at a children's cancer hospital in Pakistan. Patients were treated with modified Berlin-Frankfurt-Muenster -based therapy without risk str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 20 publications
4
42
2
Order By: Relevance
“…20 Worldwide, the global survival of pediatric patients with leukemia reveals significant differences among individuals with low income (49.8%) and with satisfactory income (62.9%). 21 In Indonesia, a diseasefree survival rate of 45% was found among those with satisfactory financial conditions, this being significantly higher than the 11% rate found among children and adolescents with low family income (p=0.01). This implies that income is a more important determinant than formal education.…”
Section: Leukemia Mortality Trends In Children and Adolescentsmentioning
confidence: 86%
See 1 more Smart Citation
“…20 Worldwide, the global survival of pediatric patients with leukemia reveals significant differences among individuals with low income (49.8%) and with satisfactory income (62.9%). 21 In Indonesia, a diseasefree survival rate of 45% was found among those with satisfactory financial conditions, this being significantly higher than the 11% rate found among children and adolescents with low family income (p=0.01). This implies that income is a more important determinant than formal education.…”
Section: Leukemia Mortality Trends In Children and Adolescentsmentioning
confidence: 86%
“…Several studies seek to discuss this theme and elucidate its probable causes. [18][19][20][21] Leukemia requires long and costly treatment, as well as requiring resources for travel to oncology centers and paying for meals and many patients -and their families -do not have social and economic support needed to maintain this routine: 19,20 16 to 50% of them abandon treatment. 18 The proportion of such abandonment differs, depending on whether country is a low-or medium-high-income country: 29% versus 2% (p<0.0001), respectively.…”
Section: Leukemia Mortality Trends In Children and Adolescentsmentioning
confidence: 99%
“…The steady progress in the development of effective treatments has led to a cure rate of more than 80% in children with ALL, most of whom will lead healthy productive lives as long-term cancer survivors (1,2). Yet, studies are underway to ascertain the precise events that take place in the genesis of ALL, to enhance the clinical application of known risk factors and anti-leukemic agents, and to identify treatment regimens that may boost the generally low cure rates in adults and subgroups of children with high-risk leukemia (3)(4)(5). Approaches aimed at blocking associated miRNAs may serve as effective therapeutic strategies for treating ALL patients and may be valuable biomarkers for diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The suboptimal outcome of our pediatric ALL patients can be explained by the socioeconomic status of the patients, lack of parental education, late diagnosis of disease, malnourishment and failure to control infections as stressed by another study on Pakistani population. 15 Another Pakistani study has shown mortality rate of 24% in childhood ALL cases (74/304 patients). The main cause of death in these patients was infection.…”
Section: Discussionmentioning
confidence: 99%